2000
DOI: 10.1103/physrevb.62.1611
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and many-particle mechanisms of two-dimensional cluster diffusion on Cu(100) surfaces

Abstract: We study the energetics and stability of small Cu clusters on Cu͑100͒ surfaces using molecular statics combined with systematic saddle-point search methods. We find several previously overlooked concerted many-particle processes that play an important role in cluster energetics. In particular, for smaller clusters there is an internal atom row shear mechanism that in some cases determines the rate-limiting step for center-ofmass motion. Our results suggest specific reaction paths for experimentally observed cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…8,[12][13][14] For fcc͑100͒ metal surfaces Shi et al 8 found in their embedded atom model ͑EAM͒ calculations a new mechanism for island diffusion through concerted dimer shearing. Most recently, Trushin et al 14,15 used sophisticated saddle-point search methods combined with EAM and showed that there are additional mechanisms such as trimer shearing at the periphery, and dimer and trimer shearing inside the island which control the RLS in some cases.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…8,[12][13][14] For fcc͑100͒ metal surfaces Shi et al 8 found in their embedded atom model ͑EAM͒ calculations a new mechanism for island diffusion through concerted dimer shearing. Most recently, Trushin et al 14,15 used sophisticated saddle-point search methods combined with EAM and showed that there are additional mechanisms such as trimer shearing at the periphery, and dimer and trimer shearing inside the island which control the RLS in some cases.…”
mentioning
confidence: 99%
“…In the previous work of SE, 17 D s was calculated up to sϭ5 including transition processes in which single atom jumps occur, and also dimer shearing was considered for tetramers. In this work, we consider dimer and trimer shearing processes for islands from five up to nine atoms as suggested by the energetics of Trushin et al 14 These results can be directly compared to the analytic formula of SE for sϭ5, and the Monte Carlo ͑MC͒ data of Heinonen et al 6 which is based on single-particle processes only.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They can even oscillate as a function of the island size [10,14,8]. These oscillations can be in part understood by the surface geometry: certain close packed island configurations can be more stable than others on certain surfaces [19]. Here we concentrate on two qualitatively and quantitatively different types of diffusion coefficients, namely those of Cu adatom islands on Cu(100) and Cu(111) surfaces.…”
Section: Diffusion Coefficientsmentioning
confidence: 99%
“…One of the most important questions that still remains open is the role of island diffusion, since for mobile islands the aggregation rates in the RE approach depend explicitly on the diffusion coefficients D s of islands of different sizes s. Island diffusion on surfaces has been studied both theoretically [7,8,9] and experimentally [10,11,12,13,14,15,16]. While in the large island limit the size dependence of the island diffusion coefficients can be classified based on simple basic processes [17], for smaller islands D s depends on the geometric and energetic details of the underlying surface, and can be a complicated, non-monotonic function of s [18,19].…”
Section: Introductionmentioning
confidence: 99%